Taxing Intermediate Goods to Compensate for Distorting Taxes on Household Consumption - Lars Bohlin (Örebro University School of Business, 2010)
In contrast to the classic result in Diamond and Mirrlees (1971) that fiscal taxes should not be levied on intermediate use of goods, Newbury (1985) showed that, in a closed economy with Leontief technology, input taxes should be used to indirectly tax commodities that for some reason are untaxed in final consumption. This paper extends the Newbury result to more general cases; i.e., to open economies with substitution possibilities in the production functions. Moreover, it shows that the welfare maximizing proportion between the tax rate for intermediate use by firms and final demand by households declines with higher elasticities of substitution in production functions and with higher price elasticities in import demand functions and export supply functions. It also shows that the welfare maximizing proportion of tax rates between households and firms for one commodity will depend upon the corresponding proportion of tax rates for important substitutes for that commodity. These results are shown both in stylized Computable General Equilibrium (CGE) models and in an applied CGE model of the Swedish economy where the tax on electricity is used as an example.
Keywords: D58; H21; 330; Optimal taxation; CGE-analysis